2017
DOI: 10.1016/j.jmoneco.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Bond finance, bank credit, and aggregate fluctuations in an open economy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…The response of real economy scale to the impact of financial scale and financial structure has significantly similar time-varying characteristics. Compared with other studies, scholars believe that the impact of the expansion of financial scale on the industrial structure presents an inverted U-shaped relationship, or other shapes [32,33,54,62], which is promoted first and then suppressed, while the empirical results of this paper show a more complex time-varying feature.…”
Section: Time-varying Impulse Response Analysis Of Different Lag Periodscontrasting
confidence: 60%
See 1 more Smart Citation
“…The response of real economy scale to the impact of financial scale and financial structure has significantly similar time-varying characteristics. Compared with other studies, scholars believe that the impact of the expansion of financial scale on the industrial structure presents an inverted U-shaped relationship, or other shapes [32,33,54,62], which is promoted first and then suppressed, while the empirical results of this paper show a more complex time-varying feature.…”
Section: Time-varying Impulse Response Analysis Of Different Lag Periodscontrasting
confidence: 60%
“…Ergungor [8] found that there is a nonlinear (contingent) relationship between growth and financial structure using a two-stage regression model, and countries that have an inflexible judicial system grow faster when they have a more bank-oriented financial system. Many scholars have also studied the interaction between financial models and the macro economy [32].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Zhou et al (2018) provided supporting evidence for the positive impact of Fintech applications on the effectiveness of credit card systems. Sun (2018) and Chang et al (2017) also underlined the importance of Fintech investments in the performance of such systems was also underlined.…”
Section: Literature On Fintechmentioning
confidence: 94%
“…value (C3)Eyal (2017),Zhou et al (2018),Sun (2018) andChang et al (2017) Non-financial (Dimension 2) Customer satisfaction (C4)Kabakova et al (2016),Komulainen et al (2018),Xu and Cheng (2017),Yao et al (2018a, b),Mittal et al (2017) andTan et al (2018) …”
mentioning
confidence: 99%
“…Finally, there is a growing macro-finance literature applying the Holmström-Tirole (1997) framework. Contributions include Chen (2001), Aikman and Paustian (2006), Meh and Moran (2010), Christensen, Meh and Moran (2011), Chang, Fernández and Gulan (2017), Faia (2018), andSilvo (2019). We extend this macro-finance framework in terms of our modeling of banks: a bank is a balance sheet structure with many bankers.…”
Section: Introductionmentioning
confidence: 99%